Stoicism or Defeat? The Psychological Impact of the Kiln Environment on Working Donkeys and Mules - Katy Taylor; Anna Harrison; Theodora Capaldo (Animals)
One of the most problematic situations for the estimated 60 million working donkeys and mules across the world is within the brick kiln environment. In countries such as Egypt, Nepal, India and Pakistan, donkeys and mules carry dried bricks into small kilns either by pulling carts or carrying loaded packs. The health and welfare problems of this environment are well documented: they may carry excessive loads; work long hours, have difficulties accessing food, water and rest options; and can frequently suffer untreated illnesses including dental problems, lameness and open wounds from poorly fitting harnesses and aggressive handlers. The impact of this environment on their mental health has been largely overlooked. We use a behavioral comparative analogy approach, comparing the clinical signs and risk factors associated with learned helplessness, depression and complex post-traumatic stress disorder (cPTSD) in humans and laboratory studies in other animals with evidence from the veterinary literature. Based on an analysis of seven quantitative veterinary studies that have evaluated the health and behavior of kiln donkeys and mules, we argue that their behavior may be consistent with learned helplessness, depression and/or cPTSD. Furthermore, the kiln environment contains many of the key environmental risk factors associated with the development of these disorders. And, because of certain behavioral differences from horses, donkeys and mules are at greater risk of their physical and mental health being overlooked. This finding, adding to the wealth of evidence for their poor health, should further strengthen efforts to replace their use in the kiln environment.